The phoenix project a novel about IT, DevOps, and helping your business win - Kim, Gene; Behr, Kevin; Spafford, George (IT Revolution, 2018)
Bill has 90 days to fix a behind-schedule IT project, or his entire department will be outsourced. Fortunately, he has the help of a prospective board member, whose "Three Ways" philosophy might just save the day.